The Influence of Eating Habits on the Incidence of Anemia in Young Women in Jogosetran Village Kalikotes-Klaten - Satiyem Satiyem; Dewi Murtiningsih (Jurnal Kesehatan Kusuma Husada, 2025)
Anemia is more common in young women. Menstruation, low nutritional intake and hemolytics are risk factors for anemia in adolescent girls. The research aims to determine the effect of consuming eggs and lime on hemoglobin levels in young women. The research was conducted in August 2024. The sample in this study was 21 young women. Non-probability sampling and determining samples using inclusion and exclusion criteria. Research Place This research was conducted in Jogosetran Village, Kalikotes Klaten. Quasi-experimental research method. Giving eating habits (lime and eggs) as an independent variable and anemia status in adolescent girls as a dependent variable. The Wilcoxon T-test was used as a two-variable analysis test. Early Adolescent Stage 19 (95%) was the age of the most respondents. Before treatment the average Hb level was 10,21 gr/dL and the most moderate anemia was 17 (81%) while after treatment the average Hb level was 12,89 gr/dL namely not anemic 17 (81%). There is a significant influence of eating habits (lime and eggs) on increasing Hb levels in adolescent girls in Jogosetran Village Kalikotes Klaten with a z score of -4,016 and a p-value 0.00.